2021
DOI: 10.3390/plants10091846
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Alternaria cerealis MT808477 Tomato Phytopathogen by Trichoderma harzianum and Tracking the Plant Physiological Changes

Abstract: Plant responses during the pathogen infection and the pathogen control reflect its strategies to protect its cells. This work represents the Alternaria cerealis MT808477 as a phytopathogen causing leaf spot disease in tomatoes. A. cerealis was identified morphologically and genetically by 18SrRNA, and its pathogenicity was confirmed by light and scanning electron microscopy. Trichoderma harzianum has the ability to control A. cerealis MT808477 by stimulating various cell responses during the controlling proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…Also, A. brassicae infection caused significant increases in phenol content in some mustard varieties (Mallick et al 2015). Regarding the interaction, a similar result indicated that phenolic compounds were accumulated in tomato plants that were infected with the pathogenic fungus A. cerealis and treated with Trichoderma harzianum compared with control plants (Mahmoud et al 2021). Moreover, phenols content significantly promoted in powdery mildew-infected berry leaves when treated with chemical fungicides (Fayez et al 2016).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Also, A. brassicae infection caused significant increases in phenol content in some mustard varieties (Mallick et al 2015). Regarding the interaction, a similar result indicated that phenolic compounds were accumulated in tomato plants that were infected with the pathogenic fungus A. cerealis and treated with Trichoderma harzianum compared with control plants (Mahmoud et al 2021). Moreover, phenols content significantly promoted in powdery mildew-infected berry leaves when treated with chemical fungicides (Fayez et al 2016).…”
Section: Discussionmentioning
confidence: 94%
“…Accumulation of these compounds in infected plants by fungal pathogens has been recorded in several studies (El-Khallal 2007 ; Ramamoorthy et al 2002 ). It was recently documented that the contents of total phenolic compounds were significantly increased in the infected tomato plants by A. cerealis in individual treatments (Mahmoud et al 2021 ). Also, A. brassicae infection caused significant increases in phenol content in some mustard varieties (Mallick et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Alternaria cerealis has been reported as a tomato pathogen in Yemen [58,59]. It is possible that our study may constitute the inaugural documentation of Alternaria cerealis and Alternaria arborescens as a pathogenic organism for tomato crops within the geographical confines of Kenya.…”
Section: Characterization Of Early Blight Pathogenmentioning
confidence: 52%
“…In the dual confrontation of T. harzianum against Fusarium sudanense , the BCA parasites the pathogen degrading its hyphae and inhibiting its growth by also competing for space and nutrients, preventing seed rot in wheat plants [ 105 ]. T. harzianum has also shown antagonistic ability in vitro during the confrontation with the pathogen Alternaria cerealis , limiting its growth [ 106 ], and the strain T. harzianum T-soybean showed mycoparasitic activity against F. oxysporum, reducing its growth by 45.45% [ 107 ].…”
Section: Biocontrol Potential Of Registered Trichoderma ...mentioning
confidence: 99%
“…A defense-related enzymatic activity such as PAL, POX, CAT, and ascorbate peroxidase is induced by inoculation with T. harzianum UBSTH-501 in wheat plants, conferring resistance against Bipolaris sorokiniana infection, and promoting SA and phenolic compounds accumulation, as well as lignin and suberization in leaves, to reinforce plant defense [ 128 ]. Upon infection of tomato plants with A. cerealis , T. harzianum induces the accumulation of different phenolic compounds, such as flavonoids and terpenoids, and increases the plant antioxidant enzymatic activity, diminishing the infection caused by A. cerealis [ 106 ]. Soybean plants treated with T. harzianum T-soybean showed less cellular death caused by F. oxysporum and increased protection against the pathogen [ 107 ].…”
Section: Biocontrol Potential Of Registered Trichoderma ...mentioning
confidence: 99%